Association of body mass index with immune recovery, virological failure and cardiovascular disease risk among people living with HIV. Issue 4 (17th November 2020) - Han, WM; Jiamsakul, A; Jantarapakde, J; Yunihastuti, E; Choi, JY; Ditangco, R; Chaiwarith, R; Sun, LP; Khusuwan, S; Merati, TP; Do, CD; Azwa, I; et al.
Abstract : Objectives: We conducted a longitudinal cohort analysis to evaluate the association of pre‐treatment body mass index (BMI) with CD4 recovery, virological failure (VF) and cardiovascular risk disease (CVD) markers among people living with HIV (PLHIV). Methods: Participants who were enrolled between January 2003 and March 2019 in a regional Asia HIV cohort with weight and height measurements prior to antiretroviral therapy (ART) initiation were included. Factors associated with mean CD4 increase were analysed using repeated‐measures linear regression. Time to first VF after 6 months on ART and time to first development of CVD risk markers were analysed using Cox regression models. Sensitivity analyses were done adjusting for Asian BMI thresholds. Results: Of 4993 PLHIV (66% male), 62% had pre‐treatment BMI in the normal range (18.5–25.0 kg/m 2 ), while 26%, 10% and 2% were underweight (< 18.5 kg/m 2 ), overweight (25–30 kg/m2) and obese (> 30 kg/m 2 ), respectively. Both higher baseline and time‐updated BMI were associated with larger CD4 gains compared with normal BMI. After adjusting for Asian BMI thresholds, higher baseline BMIs of 23–27.5 and > 27.5 kg/m 2 were associated with larger CD4 increases of 15.6 cells/µL [95% confidence interval (CI): 2.9–28.3] and 28.8 cells/µL (95% CI: 6.6–50.9), respectively, compared with normal BMI (18.5–23 kg/m 2 ). PLHIV with BMIs of 25–30 and > 30 kg/m 2 were 1.27 times (95% CI: 1.10–1.47) and 1.61 times (95% CI: 1.13–2.24) more likely to develop CVD risk factors. No relationship between pre‐treatment BMI and VF was observed. Conclusions: High pre‐treatment BMI was associated with better immune reconstitution and CVD risk factor development in an Asian PLHIV cohort.